Gold Nanorods: Encoding Random Hot Spots of a Volume Gold Nanorod Assembly for Ultralow Energy Memory (Adv. Mater. 35/2017). Issue 35 (September 2017) - Dai, Qiaofeng; Ouyang, Min; Yuan, Weiguang; Li, Jinxiang; Guo, Banghong; Lan, Sheng; Liu, Songhao; Zhang, Qiming; Lu, Guang; Tie, Shaolong; Deng, Haidong; Xu, Yi; et al.
Abstract : Hot spots with significantly enhanced electric field are generally found in plasmonic systems composed of metallic nanoparticles/nanostructures. The combination of efficient photoluminescence and polarization and wavelength sensitivity offers the opportunity to encode such hot spots for optical memory, which is a promising way of storing big data. In article number1701918, Sheng Lan, Shaolong Tie, Min Gu, and co‐workers numerically analyze the impact of hot spots on the nonlinear optical response of metallic nanoparticles/nanostructures and demonstrate multidimensional optical data storage with ultrahigh density and ultralow energy.